Comparative genomics reveal distinct potential of Tamlana sp. S12 for algal polysaccharide degradation - Xia, Hai-Feng; Jia, Xiao-Yu; Zhou, Yan-Xia; Du, Zong-Jun; Mu, Da-Shuai; Chen, Guan-Jun (Frontiers in Marine Science, 2023)
Introduction Macroalgae contain various polysaccharides that serve as nutrient sources Introduction: Macroalgae contain various polysaccharides that serve as nutrient sources for marine bacteria. Carbohydrate-active enzymes (CAZymes) are the primary feature of marine bacteria that utilize these polysaccharides. In this study, we describe Tamlana sp. S12, a novel strain of marine flavobacteria that can degrade alginate and Laminaria japonica biomass, isolated from the intestines of the sea cucumber Apostichopus japonicas collected at Weihai coast. Methods We sequenced the entire genome of strain S12 and constructed a phylogenetic tree using the core genome sequences of related strains. We determined the enzymatic activity of strain S12 using the DNS method and measured its growth curve under different carbon sources using spectrophotometry. Results Strain S12 degraded dehydrated L. japonica fragments as the sole nutrient source within 48h. Strain S12 harbors a diverse array of CAZymes at multiple polysaccharide utilization loci (PUL). One PUL encoding lyases from PL6, 7, and 17 families may be used for the degradation of alginate. Additionally, strain S12 harbors PULs encoding carrageenan- and agar-targeting CAZymes. Comparative analysis with related flavobacteria from Algibacter, Maribacter, and Zobellia showed shared CAZymes among these strains, potentially derived from a common ancestor and stably maintained within strains. Genomic signatures, algal degradation ability, and CAZyme patterns suggest that strain S12 has the potential to degrade complex algal polysaccharides. Conclusion These results expand our knowledge of CAZymes and enrich our understanding of how marine Flavobacteriaceae adapt to marine algal polysaccharide environments. The availability of the genome of Tamlana sp. S12 will be beneficial for further analyses of marine Flavobacteriaceae.